2006
DOI: 10.1385/endo:29:3:435
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gene Expression in Pituitary Carcinomas and Adenomas Analyzed by High-Density Oligonucleotide Arrays, Reverse Transcriptase-Quantitative PCR, and Protein Expression

Abstract: Very few of the genes that are important in pituitary tumor initiation, progression, and metastasis have been identified to date. To identify potential genes that may be important in pituitary tumor progression and carcinoma development, we used Affymetrix GeneChip HGU-133A-oligonucleotide arrays, which contain more than 15,000 characterized genes from the human genome to study gene expression in an ACTH pituitary carcinoma metastatic to the liver and four pituitary adenomas. Reverse-transcriptase real-time qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 54 publications
3
30
1
Order By: Relevance
“…13 Although most of these related studies reported that the Groucho/TLE family of corepressors inhibits gene expression and the signaling pathway, it also enhances the gene expression including the macrophage colony stimulating factor receptor, 14 Notch ligand Jagged1, 15 and Wnt pathway mediator plakoglobin. 16 The Groucho/ TLE family of corepressors was also suggested to be an oncogene because the over-expression of Gro/TLE family members is associated with lung adenocarcinoma, 17 grade 1 astrocytomas, 18 higher-grade meningiomas, 19 pituitary adenomas, 20,21 and synovial sarcomas, 7,22 which is consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…13 Although most of these related studies reported that the Groucho/TLE family of corepressors inhibits gene expression and the signaling pathway, it also enhances the gene expression including the macrophage colony stimulating factor receptor, 14 Notch ligand Jagged1, 15 and Wnt pathway mediator plakoglobin. 16 The Groucho/ TLE family of corepressors was also suggested to be an oncogene because the over-expression of Gro/TLE family members is associated with lung adenocarcinoma, 17 grade 1 astrocytomas, 18 higher-grade meningiomas, 19 pituitary adenomas, 20,21 and synovial sarcomas, 7,22 which is consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Our studies demonstrating low levels of TLE1 and TLE4 expression in myeloid cell lines and subsets of AML samples, and potential tumor suppressor-like activities of the Gro/TLEs, stand in contrast to recent reports that overexpression of various Gro/TLE family members is seen in grade 1 astrocytomas, 61 higher-grade meningiomas, 62 pituitary adenomas, 63,64 and synovial sarcomas. 65,66 In addition, overexpression of murine Tle1/Grg1 in a transgenic model predisposed to the development of lung adenocarcinoma.…”
contrasting
confidence: 99%
“…Several studies have used microarraybased, high-throughput gene profiling for identification of candidate genes and pituitary-specific signaling pathways that may be participate in pituitary tumorigenesis, including studies analyzing GH-secreting adenomas. 19,20,36,43 Except for genes linked to adenoma subtype, including GH and GHRH-R, 36,43 the majority of identified genes with potential tumorigenic effect are not unique to GH-secreting adenomas and seem to contribute to the pathogenesis of most adenomas (Table 1).…”
mentioning
confidence: 99%